The Digital Divide: AI Outbreak Prediction vs. The Enduring Value of Epidemiologist Analysis - Rasit Dinc (Rasit Dinc Digital Health & AI Research, 2023)
The global experience with recent pandemics has underscored the critical, life-saving necessity of accurate infectious disease forecasting. In the race again...
Keywords: Digital Health; Artificial Intelligence; Healthcare Innovation; Machine Learning; Medical Ethics